Biomethanation of agricultural residues: Potential, limitations and possible solutions. (January 2021) - Dar, R.A.; Parmar, M.; Dar, E.A.; Sani, R.K.; Phutela, U.G.
Abstract: Reasonable creation of renewable energy is being fervently debated. The biofuels, produced from food crops are restricted in their capacity to accomplish biofuel generation targets, mitigation of climate change and socio-economic development. These issues have exaggerated the curiosity in flourishing biofuels generated from non-food feedstocks like agricultural wastes, forest wastes, municipal wastes, and microalgae, which substantially offer golden opportunities in the longer run. The anaerobic digestion (AD) of agricultural residues is the potential alternate of energy production (357.85 bcm biomethane) and has the capability of reducing greenhouse gas emissions (GHG) (979 Mt CO2 eq. per year). This makes it a potential contributor to attain climate neutrality by 2050. However, the various physical, structural and compositional factors impeding the hydrolysis of agricultural residues in AD are to be eliminated. Conjoint application of biological pretreatment with other pretreatment approaches has proven to be more efficacious than applying individually. Furthermore, the well-planned policies are vital in making the AD technology adoption viable and successful. The policies regarding bioenergy production must make sure to supply food and feed items sustainably by the agricultural sector. This paper reviews the utilization of lignocellulosic agricultural wastes for biogas production, various aspects of biomethanation process like inhibitions and possible solutions for their alleviation, enhancement of biogas production, its environmental and techno-economic and policy aspects. Value addition of biodigested slurry by the production of industrial enzymes, vermicompost, fertilizer and mushroom cultivation, are also included in the paper. Highlights: Biomethanation purveys a practicable route for the management of agricultural residues. Combination of biological pretreatment with other approaches efficiently degrades biomass. Anaerobic co-digestion improves methane yield and process kinetics of AD. AD technology can potentially abate GHG emissions (979 Mt CO2 eq. per year). Enzyme production from biodigested slurry offers an efficient route for its management.